Intrinsic Static/Dynamic Energetic Disorders of Amorphous Organic Semiconductors: Microscopic Simulations and Device Study - (:unkn) unknown (AMER CHEMICAL SOC, 2021)
We report on a quantum mechanics/molecular mechanics (QM/MM) study of the static and dynamic energetic disorders of charge transport in amorphous small molecule organic semiconductors used as active carrier transport layers in various organic electronic devices. Using an ensemble-average and time-average approach on site energy modulations, we isolated the static and dynamic disorders and simulated their impact on microscopic charge transport and current-voltage characteristics using drift-diffusion equations. We found that typically one-third and two-thirds of the overall intermolecular contributions to ionization energy have a static and dynamic origin, respectively. Simulations were compared with the measured device current-voltage characteristics, and we found that static disorder is, in various levels, a significant control over carrier mobility and current density. Minimization of static disorder results in a reduced overall disorder, which is an important factor for rational organic semiconductor device optimization.
Keywords: LIGHT-EMITTING-DIODES; OPEN-CIRCUIT VOLTAGE; CHARGE-TRANSPORT; MOLECULAR MATERIALS; ELECTRON-TRANSPORT; DYNAMICS; CRYSTAL; RECOMBINATION; IMPACT; FORCE